POSSIBLE TRAJECTORIES OF INSTITUTIONAL POLICY FOR LOCAL DEVELOPMENT - Elvira Martini; Maria Carmela Serluca (Economy and Sociology)
Relationships between the actors who live on a territory are very important when one want to conduct an analysis centred on the theme of local development and its sustainability. In fact, these actors - and the social relationships that they build and support - choose the most appropriate resources to enable development mechanisms. At the same time, the actors decide what are the costs of sustainable development and who should participate in the efforts in order to favour the growth and to share successes. In other words, local development policies require a strong and high profile intervention by the public actor, even when their realization necessarily involves collaboration with private actors. Based on these statements the aim of this paper is - from one side - to highlight the cognitive strategies that enable actors to support institutional development and growth of a territory, with particular reference to the implementation of invisible factors such as the social capital, the construction and socialization of new knowledge, the good practices of a territorial management based on the principles of good governance. On the other hand, we want to show - more closely and specifically - what are the correlations (we hope the positive ones) between the work of the Public Administration and the development’s level of a territory, whereas the current system complexity requires that the structural measures of the Public Administration should be guided by the objective of pursuing higher levels of efficiency together to the needs of public expenditure.